Preparation method of composite solid electrolyte nanofiber membrane, fiber membrane and application thereof

CN122992162APending Publication Date: 2026-10-27DONGHUA UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611478562.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-22
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

[0003]目前已研发的固态电解质纤维材料存在明显性能短板,难以兼顾实际应用所需的综合性能:氧化物固态电解质纤维拥有较高的机械强度和化学稳定性,但其离子电导率偏低,无法达到的商用电导率标准,制约了电池的倍率性能;硫化物固态电解质纤维的离子电导率表现优异,却存在机械强度低、结构稳定性差的问题,且该类材料遇水易发生分解并产生有毒气体,增加了制备、储存和使用过程中的管控难度与安全风险;卤化物固态电解质纤维虽同样具备高离子电导率的优势,但其机械强度不足,难以有效抵御锂枝晶穿刺,无法保障电池的长期使用安全

Benefits of technology

1、制备工艺层面,采用廉价原料并通过前驱体溶液静电纺丝、分步煅烧烧结的方式制备,相较传统高温固相法大幅降低了合成温度与制备周期,显著降低了生产使用成本;

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122992162A_ABST
    Figure CN122992162A_ABST
Patent Text Reader

Abstract

The application discloses a preparation method of a composite solid-state electrolyte nanofiber membrane, the fiber membrane and application thereof, and belongs to the solid-state electrolyte field and comprises the following steps: S1, preparing an oxide solid-state electrolyte precursor solution; S2, electrospinning to prepare a precursor fiber membrane; S3, air calcination to prepare an oxide solid-state electrolyte fiber membrane; S4, preparing a halide solid-state electrolyte precursor solution; S5, soaking the pure-phase oxide solid-state electrolyte nanofiber membrane in the halide solid-state electrolyte precursor solution to obtain a fiber membrane coated with a halide precursor; and S6, sintering in a protective atmosphere to prepare a core-shell structure fiber membrane. The preparation method of the composite solid-state electrolyte nanofiber membrane, the fiber membrane and application thereof are simple in process and low in cost, realize the performance compromise of high mechanical strength, good flexibility and high ionic conductivity, and effectively solve the performance short board of existing solid-state electrolyte fibers.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of solid electrolyte technology, and in particular to a method for preparing composite solid electrolyte nanofiber membranes, the nanofiber membranes, and their applications. Background Technology

[0002] Lithium-ion batteries, as a new generation of energy storage devices, are widely used in various electronic devices, new energy vehicles, and energy storage systems. Currently, most commercially available lithium-ion batteries use organic liquid electrolyte systems. However, these electrolytes have inherent safety hazards such as flammability and explosiveness, and are prone to causing safety accidents under conditions of overcharging, short circuits, or high temperatures, severely limiting the application of lithium-ion batteries in fields with high safety requirements. Solid-state electrolytes, due to their non-flammable properties, can fundamentally solve the safety defects of organic liquid electrolytes. At the same time, they can effectively inhibit the growth and penetration of lithium dendrites, significantly improving the cycle stability and safety of lithium-ion batteries, making them an important development direction in the field of lithium-ion battery electrolytes.

[0003] Currently developed solid electrolyte fiber materials have significant performance shortcomings, making it difficult to achieve the comprehensive performance required for practical applications: oxide solid electrolyte fibers possess high mechanical strength and chemical stability, but their ionic conductivity is relatively low, failing to meet the requirements. Commercial conductivity standards limit the rate performance of batteries. Sulfide solid electrolyte fibers have excellent ionic conductivity, but they suffer from low mechanical strength and poor structural stability. Moreover, these materials are prone to decomposition and the generation of toxic gases when exposed to water, which increases the difficulty of control and safety risks during preparation, storage and use. Halide solid electrolyte fibers also have the advantage of high ionic conductivity, but their mechanical strength is insufficient and they cannot effectively resist lithium dendrite puncture, thus failing to ensure the long-term safety of battery use. Summary of the Invention

[0004] The purpose of this invention is to provide a method for preparing composite solid electrolyte nanofiber membranes, the nanofiber membranes and their applications, thereby solving the aforementioned technical problems.

[0005] To achieve the above objectives, the present invention provides a method for preparing a composite solid electrolyte nanofiber membrane, comprising the following steps: S1. Preparation of oxide solid electrolyte precursor solution: Mix the metal source, polymer and organic solvent required for oxide solid electrolyte and stir evenly to obtain a uniform oxide solid electrolyte precursor solution. S2. Preparation of precursor fiber membrane by electrospinning: The oxide solid electrolyte precursor solution obtained in S1 is electrospinned. During the spinning process, a constant temperature hot field of 20℃-80℃ is applied in the spinning zone, while the temperature of the receiving device is controlled at 10℃-40℃ to obtain the oxide solid electrolyte precursor fiber membrane. S3. Preparation of oxide solid electrolyte fiber membrane by air calcination: The oxide solid electrolyte precursor fiber membrane obtained in S2 is placed in an air atmosphere for calcination, so that the polymer is removed by pyrolysis and the metal source is oxidized and crystallized, and a pure phase oxide solid electrolyte nanofiber membrane is obtained. S4. Preparation of halide solid electrolyte precursor solution: Mix the metal source required for halide solid electrolyte with organic solvent and stir evenly to obtain a homogeneous halide solid electrolyte precursor solution. S5. Immersion and Coating: The pure phase oxide solid electrolyte nanofiber membrane obtained in S3 is immersed in the halide solid electrolyte precursor solution obtained in S4. The halide precursor is uniformly adsorbed and coated on the surface of the oxide nanofiber by capillary action to obtain a fiber membrane coated with halide precursor. S6. Preparation of core-shell structured fiber membrane by sintering under protective atmosphere: The fiber membrane coated with halide precursor obtained in S5 is placed in an inert protective atmosphere for low-temperature sintering, so that the halide precursor crystallizes to form a dense halide solid electrolyte coating layer, thus obtaining a core-shell structured composite solid electrolyte nanofiber membrane with an inner layer of oxide solid electrolyte and an outer layer of halide solid electrolyte.

[0006] Preferably, the molar ratio of the metal source to the polymer and organic solvent required for the oxide solid electrolyte in step S1 is (1.3~10):(0.01~0.09):(15~920), the stirring temperature is 25℃-80℃, and the stirring time is 50min-120min.

[0007] Preferably, the metal source required for the oxide solid electrolyte in step S1 is a lithium salt or metal acid salt corresponding to LLZO, LATP, or LLTO. Among them, the metal source corresponding to LLZO is a combination of lithium salt, lanthanum salt and zirconium salt, the lithium salt is lithium chloride, the lanthanum salt is lanthanum chloride, the zirconium salt is zirconium chloride, and the molar ratio of lithium salt, lanthanum salt, zirconium salt, polymer and organic solvent is 7:3:2:0.02:500. The metal source corresponding to LLTO is a combination of lithium salt, lanthanum salt and titanium salt. The lithium salt is lithium chloride, the lanthanum salt is lanthanum chloride, and the titanium salt is zirconium acetate. The molar ratio of lithium salt, lanthanum salt, titanium salt, polymer and organic solvent is 3.4:5.6:10:0.09:920. The metal source corresponding to LATP is a combination of lithium salt, aluminum salt, titanium salt and phosphorus source. The lithium salt is lithium nitrate, the aluminum salt is aluminum nitrate, the titanium salt is titanium nitrate, and the phosphorus source is phosphoric acid. The molar ratio of lithium salt, aluminum salt, titanium salt, phosphorus source, polymer and solvent is 1.3∶0.3∶1.7∶3∶0.01∶500.

[0008] Preferably, the polymer in step S1 is one of polyvinylpyrrolidone, polyvinyl butyral, or polyvinylidene fluoride. The organic solvent mentioned in step S1 is ethanol or N,N-dimethylformamide.

[0009] Preferably, the electrospinning process parameters in step S2 are: relative humidity 20%-60%, oxide solid electrolyte precursor solution injection rate 1mL / h-3mL / h, spinning voltage 25kV-40kV, distance between receiving device and spinneret 30cm-40cm, and receiving device rotation speed 50r / min-80r / min. The receiving device is a metal roller, and the precursor fiber membrane obtained by electrospinning has a continuous nanofiber interwoven structure, which provides high specific surface area support for the uniform formation of the subsequent core-shell structure.

[0010] Preferably, in step S3, the calcination heating rate is 3℃ / min-10℃ / min, the final calcination temperature is 780℃-900℃, and the holding time at the final temperature is 60min-120min.

[0011] Preferably, the metal source required for the halide solid electrolyte in step S4 is a combination of lithium source and indium source corresponding to LYC, LZC or LNOC, wherein the lithium source is lithium chloride, the indium source is indium chloride, and the molar ratio of lithium chloride to indium chloride is 3:1. The organic solvent mentioned in step S4 is ethanol or tetrahydrofuran.

[0012] Preferably, in step S5, the impregnation time is 60 min-80 min, so that the halide precursor forms a uniform coating layer without gaps on the surface of the oxide fiber; In step S6, the inert protective atmosphere is nitrogen, the sintering heating rate is 5℃ / min, the final sintering temperature is 350~400℃, and the holding time at the final temperature is 120min.

[0013] The fiber membrane prepared by the method of composite solid electrolyte nanofiber membrane is a core-shell structured composite solid electrolyte nanofiber membrane. The core-shell structure comprises a core layer composed of oxide solid electrolyte nanofibers and a shell layer composed of halide solid electrolyte nanofibers. The average fiber diameter is 450 nm-480 nm, and the ionic conductivity reaches 1.3 × 10⁻⁶. -3 -3.6×10 -3 S / cm.

[0014] Application of fiber membranes in flexible solid-state batteries.

[0015] Therefore, the present invention, employing the above-mentioned method for preparing composite solid electrolyte nanofiber membranes, the fiber membranes, and their applications, has the following beneficial effects: 1. In terms of preparation process, it uses inexpensive raw materials and prepares the product through electrospinning of precursor solution and stepwise calcination and sintering. Compared with the traditional high-temperature solid-state method, it significantly reduces the synthesis temperature and preparation cycle, and significantly reduces the production and use costs. 2. In terms of mechanical performance, the oxide core layer in the core-shell structure provides high mechanical strength and structural stability, while the halide shell layer gives the fiber membrane good flexibility. The tight combination of the core and shell makes the fiber membrane have both bending and tensile strength properties, which meets the requirements for the use of flexible solid-state lithium batteries. 3. In terms of ion conduction, the halide shell effectively compensates for the insufficient ionic conductivity of oxide solid electrolytes, and the prepared fiber membrane achieves an ionic conductivity of 10. -3 The commercial conductivity standard of S / cm improves the ion transport efficiency of batteries; 4. In terms of battery safety, the all-solid electrolyte contains no organic liquid components, which fundamentally solves the problems of flammability and explosion of liquid electrolytes; the rigid structure of the oxide core layer can effectively inhibit the growth and puncture of lithium dendrites, and at the same time block foreign particles, greatly improving the safety of lithium-ion batteries. 5. In terms of interface performance, the halide shell optimizes the interfacial compatibility between the electrolyte and the positive and negative electrodes of the lithium battery. The core and shell are tightly wrapped without obvious phase separation, which eliminates the interface transport bottleneck, reduces grain boundary impedance and interfacial side reactions, and improves the cycle stability of the battery. 6. In terms of application prospects, the prepared core-shell structured composite solid electrolyte nanofiber membrane has excellent comprehensive performance and has broad practical application value in the fields of all-solid-state lithium batteries and flexible lithium batteries, providing a feasible technical solution for the industrialization of solid-state lithium batteries.

[0016] The technical solution of the present invention will be further described in detail below with reference to the accompanying drawings and embodiments. Attached Figure Description

[0017] Figure 1 This is a flowchart of the preparation method of the composite solid electrolyte nanofiber membrane according to the present invention; Figure 2 The image shows a SEM image of the fiber membrane prepared by the method for preparing the composite solid electrolyte nanofiber membrane described in Example 1 of this invention. Detailed Implementation

[0018] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the embodiments of the present invention will be further described in detail below with reference to the accompanying drawings and examples. It should be understood that the specific embodiments described herein are merely illustrative of the embodiments of the present invention and are not intended to limit the embodiments of the present invention. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention without creative effort are within the scope of protection of this application. Examples of the embodiments are shown in the accompanying drawings, wherein the same or similar reference numerals denote the same or similar elements or elements having the same or similar functions throughout.

[0019] It should be noted that the terms "comprising" and "having," and any variations thereof, are intended to cover non-exclusive inclusion, such as a process, method, system, product, or server that includes a series of steps or units, not necessarily limited to those steps or units explicitly listed, but may include other steps or units not explicitly listed or inherent to such process, method, product, or device.

[0020] The embodiments of the present invention will now be described in detail with reference to the accompanying drawings.

[0021] like Figure 1 and Figure 2 As shown, the preparation method of the composite solid electrolyte nanofiber membrane includes the following steps: S1. Preparation of oxide solid electrolyte precursor solution: Mix the metal source, polymer and organic solvent required for oxide solid electrolyte and stir evenly to obtain a uniform oxide solid electrolyte precursor solution. S2. Preparation of precursor fiber membrane by electrospinning: The oxide solid electrolyte precursor solution obtained in S1 is electrospinned. During the spinning process, a constant temperature hot field of 20℃-80℃ is applied in the spinning zone, while the temperature of the receiving device is controlled at 10℃-40℃ to obtain the oxide solid electrolyte precursor fiber membrane. S3. Preparation of oxide solid electrolyte fiber membrane by air calcination: The oxide solid electrolyte precursor fiber membrane obtained in S2 is placed in an air atmosphere for calcination, so that the polymer is removed by pyrolysis and the metal source is oxidized and crystallized, and a pure phase oxide solid electrolyte nanofiber membrane is obtained. S4. Preparation of halide solid electrolyte precursor solution: Mix the metal source required for halide solid electrolyte with organic solvent and stir evenly to obtain a homogeneous halide solid electrolyte precursor solution. S5. Immersion and Coating: The pure phase oxide solid electrolyte nanofiber membrane obtained in S3 is immersed in the halide solid electrolyte precursor solution obtained in S4. The halide precursor is uniformly adsorbed and coated on the surface of the oxide nanofiber by capillary action to obtain a fiber membrane coated with halide precursor. S6. Preparation of core-shell structured fiber membrane by sintering under protective atmosphere: The fiber membrane coated with halide precursor obtained in S5 is placed in an inert protective atmosphere for low-temperature sintering, so that the halide precursor crystallizes to form a dense halide solid electrolyte coating layer, thus obtaining a core-shell structured composite solid electrolyte nanofiber membrane with an inner layer of oxide solid electrolyte and an outer layer of halide solid electrolyte.

[0022] The molar ratio of the metal source to the polymer and organic solvent required for the oxide solid electrolyte in step S1 is (1.3~10):(0.01~0.09):(15~920), the stirring temperature is 25℃-80℃, and the stirring time is 50min-120min.

[0023] The metal source required for the oxide solid electrolyte in step S1 is lithium salt or metal acid salt material corresponding to LLZO, LATP or LLTO; Among them, LLZO (lithium lanthanum zirconium oxide, Li7La3Zr2O) 12 The corresponding metal source is a combination of lithium salt, lanthanum salt and zirconium salt, where lithium salt is lithium chloride, lanthanum salt is lanthanum chloride and zirconium salt is zirconium chloride, and the molar ratio of lithium salt, lanthanum salt, zirconium salt, polymer and organic solvent is 7:3:2:0.02:500. LLTO (Lithium Lanthanum Titanium Oxide, Li 0.31 La 0.56 TiO3 / Li 0.34 La 0.56 The metal source corresponding to TiO3 is a combination of lithium salt, lanthanum salt and titanium salt, with lithium salt being lithium chloride, lanthanum salt being lanthanum chloride and titanium salt being zirconium acetate, and the molar ratio of lithium salt, lanthanum salt, titanium salt, polymer and organic solvent being 3.4∶5.6∶10∶0.09∶920. LATP (Lithium Aluminum Titanium Phosphate Oxide, Li 1.3 Al 0.3 Ti 1.7 (PO4)3) The corresponding metal source is a combination of lithium salt, aluminum salt, titanium salt and phosphorus source. The lithium salt is lithium nitrate, the aluminum salt is aluminum nitrate, the titanium salt is titanium nitrate, and the phosphorus source is phosphoric acid. The molar ratio of lithium salt, aluminum salt, titanium salt, phosphorus source, polymer and solvent is 1.3∶0.3∶1.7∶3∶0.01∶500.

[0024] The polymer mentioned in step S1 is one of polyvinylpyrrolidone, polyvinyl butyral, or polyvinylidene fluoride. The organic solvent mentioned in step S1 is ethanol or N,N-dimethylformamide.

[0025] Preferably, the electrospinning process parameters in step S2 are: relative humidity 20%-60%, oxide solid electrolyte precursor solution injection rate 1mL / h-3mL / h, spinning voltage 25kV-40kV, distance between receiving device and spinneret 30cm-40cm, and receiving device rotation speed 50r / min-80r / min. The receiving device is a metal roller, and the precursor fiber membrane obtained by electrospinning has a continuous nanofiber interwoven structure, which provides high specific surface area support for the uniform formation of the subsequent core-shell structure.

[0026] In step S3, the calcination heating rate is 3℃ / min-10℃ / min, the final calcination temperature is 780℃-900℃, and the holding time at the final temperature is 60min-120min. Through precise temperature control calcination, the metal source is fully crystallized, while fiber cracking is avoided, ensuring the mechanical strength and structural integrity of the oxide core layer, and providing a rigid support framework for the subsequent halide coating layer.

[0027] The metal source required for the halide solid electrolyte in step S4 is a combination of lithium source and indium source corresponding to LYC, LZC or LNOC, wherein the lithium source is lithium chloride, the indium source is indium chloride, and the molar ratio of lithium chloride to indium chloride is 3:1. The organic solvent mentioned in step S4 is ethanol or tetrahydrofuran.

[0028] In step S5, the immersion time is 60min-80min, so that the halide precursor forms a uniform coating layer without gaps on the surface of the oxide fiber, eliminating the core-shell interface gap and reducing the interface impedance for subsequent ion transport. In step S6, the inert protective atmosphere is nitrogen, the sintering heating rate is 5℃ / min, the final sintering temperature is 350~400℃, and the holding time at the final temperature is 120min. Low-temperature sintering crystallizes the halide precursor while preventing the halide from oxidizing and decomposing and diffusing into the oxide core layer, thus ensuring the clarity of the core-shell structure and the strength of the interface bonding.

[0029] The fiber membrane prepared by the method of composite solid electrolyte nanofiber membrane is a core-shell structured composite solid electrolyte nanofiber membrane. The core-shell structure comprises a core layer composed of oxide solid electrolyte nanofibers and a shell layer composed of halide solid electrolyte nanofibers. The average fiber diameter is 450 nm-480 nm, and the ionic conductivity reaches 1.3 × 10⁻⁶. -3 -3.6×10 -3S / cm, combining high mechanical strength, good flexibility, and excellent lithium-ion conductivity. This means that the tightly encapsulated interface between the core and shell exhibits no significant phase separation. The rigid structure of the oxide core provides support for the halide shell, preventing structural collapse of the halide under stress. The halide shell completely encapsulates the oxide core, eliminating interfacial impedance between the oxide and the electrode, forming an integrated system of "structural support + rapid conduction".

[0030] Application of fiber membranes in flexible solid-state batteries.

[0031] To further disclose the present invention, the following three embodiments are added.

[0032] Example 1: Preparation of LLZO / Li3InCl6 core-shell structured composite solid electrolyte nanofiber membrane.

[0033] The specific steps are as follows: S1. Preparation of oxide solid electrolyte precursor solution: Polyvinylpyrrolidone (Aladdin, molecular weight 1,300,000) was dissolved in ethanol at 25°C and stirred for 50 min. Then, lithium chloride, lanthanum chloride and zirconium chloride were added in sequence and stirred for 120 min to obtain a homogeneous precursor solution. The molar ratio of lithium salt, lanthanum salt, zirconium salt, polymer and organic solvent was 7:3:2:0.02:500. S2. Preparation of precursor fiber membrane by electrospinning: The precursor solution obtained in S1 is electrospinned. During the spinning process, a constant temperature hot field of 60°C is applied in the spinning zone and the temperature of the metal roller receiving device is controlled at 25°C. The process parameters of electrospinning are: relative humidity 60%, infusion rate 1mL / h, spinning voltage 30kV, distance between receiving device and spinneret 40cm, and rotation speed of receiving device 50r / min, to obtain oxide solid electrolyte precursor fiber membrane. S3. Preparation of oxide solid electrolyte fiber membrane by air calcination: The precursor fiber membrane obtained in S2 was calcined in an air atmosphere. The calcination temperature was gradually increased from room temperature to 810℃ at a rate of 3℃ / min, and held at 810℃ for 60min to allow the polyvinylpyrrolidone to be pyrolyzed and removed, and the metal source to be oxidized and crystallized, thus obtaining pure phase LLZO (lithium lanthanum zirconium oxide, Li7La3Zr2O). 12 Solid electrolyte nanofiber membrane; S4. Preparation of halide solid electrolyte precursor solution: At 25°C, lithium chloride source and indium chloride source are added sequentially to organic solvent ethanol, and stirred for 120 min to mix evenly to obtain a homogeneous precursor solution, wherein the molar ratio of lithium source, indium source and organic solvent is 3:1:15. S5. Immersion and Coating: The LLZO solid electrolyte nanofiber membrane obtained in S3 is immersed in the halide solid electrolyte precursor solution obtained in S4 for 80 min. The halide precursor is uniformly adsorbed and coated on the surface of the oxide nanofiber by capillary action to obtain a fiber membrane coated with halide precursor. S6. Preparation of core-shell structured fiber membrane by sintering under protective atmosphere: The fiber membrane coated with halide precursor obtained in S5 was sintered in a nitrogen inert protective atmosphere. The sintering temperature was gradually increased from room temperature to 350℃ at a heating rate of 5℃ / min, and held at 350℃ for 120min to allow the halide precursor to crystallize and form a dense halide solid electrolyte coating layer, thus obtaining an LLZO / Li3InCl6 core-shell structured composite solid electrolyte nanofiber membrane.

[0034] The core-shell structured solid electrolyte nanofiber film prepared in this embodiment has an average fiber diameter of 450 nm as measured by scanning electron microscopy, and an ionic conductivity of 3.6 × 10⁻⁶ as measured by AC impedance spectroscopy. -3 S / cm.

[0035] Example 2: Preparation of LLTO / Li2InCl6 core-shell structured composite solid electrolyte nanofiber membrane.

[0036] The specific steps are as follows: S1. Preparation of oxide solid electrolyte precursor solution: Polyvinyl butyral (Aladdin, molecular weight 170,000-250,000) was dissolved in ethanol at 25°C and stirred for 80 min. Then, lithium chloride, lanthanum chloride, and zirconium acetate were added sequentially and stirred for another 120 min to obtain a homogeneous precursor solution. The molar ratio of lithium source, lanthanum source, titanium source, polymer and organic solvent was 3.4:5.6:10:0.09:920. S2. Preparation of precursor fiber membrane by electrospinning: The precursor solution obtained in S1 was electrospinned. During the spinning process, a constant temperature hot field of 45°C was applied in the spinning zone and the temperature of the metal roller receiving device was controlled at 35°C. The process parameters for electrospinning were: relative humidity 20%, infusion rate 1.5 mL / h, spinning voltage 25 kV, distance between the receiving device and the spinneret 30 cm, and rotation speed of the receiving device 70 r / min. The oxide solid electrolyte precursor fiber membrane was thus obtained. S3. Preparation of oxide solid electrolyte fiber membrane by air calcination: The precursor fiber membrane obtained in S2 was calcined in an air atmosphere. The calcination temperature was gradually increased from room temperature to 780℃ at a heating rate of 5℃ / min, and held at 780℃ for 120min to allow the polyvinyl butyral to be pyrolyzed and removed, and the metal source to be oxidized and crystallized, thus obtaining pure-phase LLTO (lithium lanthanum titanium oxide, Li...). 0.34 La0.56 TiO3 solid electrolyte nanofiber membrane; S4. Preparation of halide solid electrolyte precursor solution: At 25°C, lithium chloride source and indium chloride source are added sequentially to organic solvent ethanol, and stirred for 120 min to mix evenly to obtain a homogeneous precursor solution, wherein the molar ratio of lithium source, indium source and organic solvent is 3:1:15. S5. Immersion and Coating: The LLTO solid electrolyte nanofiber membrane obtained in S3 is immersed in the halide solid electrolyte precursor solution obtained in S4 for 60 min. The halide precursor is uniformly adsorbed and coated on the surface of the oxide nanofiber by capillary action to obtain a fiber membrane coated with halide precursor. S6. Preparation of core-shell structured fiber membrane by sintering under protective atmosphere: The fiber membrane coated with halide precursor obtained in S5 was sintered in a nitrogen inert protective atmosphere. The sintering temperature was gradually increased from room temperature to 400℃ at a heating rate of 5℃ / min, and held at 400℃ for 120min to allow the halide precursor to crystallize and form a dense halide solid electrolyte coating layer, thus obtaining an LLTO / Li2InCl6 core-shell structured composite solid electrolyte nanofiber membrane.

[0037] The core-shell structured solid electrolyte nanofiber film prepared in this embodiment has an average fiber diameter of 480 nm as measured by scanning electron microscopy, and an ionic conductivity of 1.3 × 10⁻⁶ as measured by AC impedance spectroscopy. -3 S / cm.

[0038] Example 3: Preparation of LATP / Li2InCl6 core-shell composite solid electrolyte nanofiber membrane.

[0039] The specific steps are as follows: S1. Preparation of oxide solid electrolyte precursor solution: Polyvinylidene fluoride (Alfaea, molecular weight 570,000) was dissolved in organic solvent N,N-dimethylformamide at 80℃ and stirred for 60 min. Then, lithium nitrate, aluminum nitrate, titanium nitrate and phosphoric acid were added sequentially and stirred for another 60 min to obtain a homogeneous precursor solution. The molar ratio of lithium source, aluminum source, titanium source, phosphoric acid source, polymer and organic solvent was 1.3∶0.3∶1.7∶3∶0.01∶500. S2. Preparation of precursor fiber membrane by electrospinning: The precursor solution obtained in S1 is electrospinned. During the spinning process, a constant temperature hot field of 30°C is applied in the spinning zone and the temperature of the metal roller receiving device is controlled at 35°C. The process parameters of electrospinning are: relative humidity 45%, infusion rate 3mL / h, spinning voltage 40kV, distance between receiving device and spinneret 40cm, and rotation speed of receiving device 80r / min. The oxide solid electrolyte precursor fiber membrane is obtained. S3. Preparation of oxide solid electrolyte fiber membrane by air calcination: The precursor fiber membrane obtained in S2 was calcined in an air atmosphere. The calcination temperature was gradually increased from room temperature to 900℃ at a rate of 10℃ / min, and held at 900℃ for 60min to allow the polyvinylidene fluoride to be pyrolyzed and the metal source to be oxidized and crystallized, thus obtaining pure-phase LATP (lithium aluminum titanium phosphorus oxide, Li...). 1.3 Al 0.3 Ti 1.7 (PO4)3) Solid electrolyte nanofiber membrane; S4. Preparation of halide solid electrolyte precursor solution: At 25°C, lithium chloride source and indium chloride source are added sequentially to the organic solvent tetrahydrofuran, and stirred for 120 min to mix evenly to obtain a homogeneous precursor solution, wherein the molar ratio of lithium source, indium source and organic solvent is 3:1:15. S5. Immersion and Coating: The LATP solid electrolyte nanofiber membrane obtained in S3 is immersed in the halide solid electrolyte precursor solution obtained in S4 for 80 min. The halide precursor is uniformly adsorbed and coated on the surface of the oxide nanofiber by capillary action to obtain a fiber membrane coated with halide precursor. S6. Preparation of core-shell structured fiber membrane by sintering under protective atmosphere: The fiber membrane coated with halide precursor obtained in S5 was sintered in a nitrogen inert protective atmosphere. The sintering temperature was gradually increased from room temperature to 400℃ at a heating rate of 5℃ / min, and held at 400℃ for 120min to allow the halide precursor to crystallize and form a dense halide solid electrolyte coating layer, thus obtaining LATP / Li2InCl6 core-shell structured composite solid electrolyte nanofiber membrane.

[0040] The core-shell structured solid electrolyte nanofiber film prepared in this embodiment has an average fiber diameter of 470 nm as measured by scanning electron microscopy, and an ionic conductivity of 3.3 × 10⁻⁶ as measured by AC impedance spectroscopy. -3 S / cm.

[0041] The core-shell structured composite solid electrolyte nanofiber membranes prepared in Examples 1-3 above have an average fiber diameter of 450 nm-480 nm and an ionic conductivity of 1.3 × 10⁻⁶. -3 -3.6×10 -3 Both S / cm have high mechanical strength, good flexibility and excellent lithium-ion conductivity, and can be applied to flexible solid-state batteries.

[0042] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and not to limit them. Although the present invention has been described in detail with reference to preferred embodiments, those skilled in the art should understand that modifications or equivalent substitutions can still be made to the technical solutions of the present invention, and these modifications or equivalent substitutions cannot cause the modified technical solutions to deviate from the spirit and scope of the technical solutions of the present invention.

Claims

1. A method for preparing a composite solid electrolyte nanofiber membrane, characterized in that: Includes the following steps: S1. Preparation of oxide solid electrolyte precursor solution: Mix the metal source, polymer and organic solvent required for oxide solid electrolyte and stir evenly to obtain a uniform oxide solid electrolyte precursor solution. S2. Preparation of precursor fiber membrane by electrospinning: The oxide solid electrolyte precursor solution obtained in S1 is electrospinned. During the spinning process, a constant temperature hot field of 20℃-80℃ is applied in the spinning zone, while the temperature of the receiving device is controlled at 10℃-40℃ to obtain the oxide solid electrolyte precursor fiber membrane. S3. Preparation of oxide solid electrolyte fiber membrane by air calcination: The oxide solid electrolyte precursor fiber membrane obtained in S2 is placed in an air atmosphere for calcination, so that the polymer is removed by pyrolysis and the metal source is oxidized and crystallized, and a pure phase oxide solid electrolyte nanofiber membrane is obtained. S4. Preparation of halide solid electrolyte precursor solution: Mix the metal source required for halide solid electrolyte with organic solvent and stir evenly to obtain a homogeneous halide solid electrolyte precursor solution. S5. Immersion and Coating: The pure phase oxide solid electrolyte nanofiber membrane obtained in S3 is immersed in the halide solid electrolyte precursor solution obtained in S4. The halide precursor is uniformly adsorbed and coated on the surface of the oxide nanofiber by capillary action to obtain a fiber membrane coated with halide precursor. S6. Preparation of core-shell structured fiber membrane by sintering under protective atmosphere: The fiber membrane coated with halide precursor obtained in S5 is placed in an inert protective atmosphere for low-temperature sintering, so that the halide precursor crystallizes to form a dense halide solid electrolyte coating layer, thus obtaining a core-shell structured composite solid electrolyte nanofiber membrane with an inner layer of oxide solid electrolyte and an outer layer of halide solid electrolyte.

2. The method for preparing the composite solid electrolyte nanofiber membrane according to claim 1, characterized in that: The molar ratio of the metal source to the polymer and organic solvent required for the oxide solid electrolyte in step S1 is (1.3~10):(0.01~0.09):(15~920), the stirring temperature is 25℃-80℃, and the stirring time is 50min-120min.

3. The method for preparing the composite solid electrolyte nanofiber membrane according to claim 2, characterized in that: The metal source required for the oxide solid electrolyte in step S1 is lithium salt or metal acid salt material corresponding to LLZO, LATP or LLTO; Among them, the metal source corresponding to LLZO is a combination of lithium salt, lanthanum salt and zirconium salt, the lithium salt is lithium chloride, the lanthanum salt is lanthanum chloride, the zirconium salt is zirconium chloride, and the molar ratio of lithium salt, lanthanum salt, zirconium salt, polymer and organic solvent is 7:3:2:0.02:

500. The metal source corresponding to LLTO is a combination of lithium salt, lanthanum salt and titanium salt. The lithium salt is lithium chloride, the lanthanum salt is lanthanum chloride, and the titanium salt is zirconium acetate. The molar ratio of lithium salt, lanthanum salt, titanium salt, polymer and organic solvent is 3.4:5.6:10:0.09:

920. The metal source corresponding to LATP is a combination of lithium salt, aluminum salt, titanium salt and phosphorus source. The lithium salt is lithium nitrate, the aluminum salt is aluminum nitrate, the titanium salt is titanium nitrate, and the phosphorus source is phosphoric acid. The molar ratio of lithium salt, aluminum salt, titanium salt, phosphorus source, polymer and solvent is 1.3∶0.3∶1.7∶3∶0.01∶500.

4. The method for preparing the composite solid electrolyte nanofiber membrane according to claim 1, characterized in that: The polymer mentioned in step S1 is one of polyvinylpyrrolidone, polyvinyl butyral, or polyvinylidene fluoride. The organic solvent mentioned in step S1 is ethanol or N,N-dimethylformamide.

5. The method for preparing the composite solid electrolyte nanofiber membrane according to claim 1, characterized in that: The electrospinning process parameters described in step S2 are: relative humidity 20%-60%, oxide solid electrolyte precursor solution injection rate 1mL / h-3mL / h, spinning voltage 25kV-40kV, distance between receiving device and spinneret 30cm-40cm, and receiving device rotation speed 50r / min-80r / min. The receiving device is a metal roller, and the precursor fiber membrane obtained by electrospinning has a continuous nanofiber interwoven structure, which provides high specific surface area support for the uniform formation of the subsequent core-shell structure.

6. The method for preparing the composite solid electrolyte nanofiber membrane according to claim 1, characterized in that: In step S3, the heating rate of calcination is 3℃ / min-10℃ / min, the final calcination temperature is 780℃-900℃, and the holding time at the final temperature is 60min-120min.

7. The method for preparing the composite solid electrolyte nanofiber membrane according to claim 1, characterized in that: The metal source required for the halide solid electrolyte in step S4 is a combination of lithium source and indium source corresponding to LYC, LZC or LNOC, wherein the lithium source is lithium chloride, the indium source is indium chloride, and the molar ratio of lithium chloride to indium chloride is 3:

1. The organic solvent mentioned in step S4 is ethanol or tetrahydrofuran.

8. The method for preparing the composite solid electrolyte nanofiber membrane according to claim 5, characterized in that: In step S5, the impregnation time is 60 min-80 min, so that the halide precursor forms a uniform coating layer without gaps on the surface of the oxide fiber. In step S6, the inert protective atmosphere is nitrogen, the sintering heating rate is 5℃ / min, the final sintering temperature is 350~400℃, and the holding time at the final temperature is 120min.

9. The fiber membrane prepared by the method for preparing the composite solid electrolyte nanofiber membrane according to any one of claims 1-8, characterized in that: The fiber membrane is a core-shell structured composite solid electrolyte nanofiber membrane, comprising a core layer composed of oxide solid electrolyte nanofibers and a shell layer composed of halide solid electrolyte nanofibers. The average fiber diameter is 450 nm–480 nm, and the ionic conductivity reaches 1.3 × 10⁻⁶. -3 -3.6×10 -3 S / cm.

10. The application of the fiber membrane as described in claim 9 in a flexible solid-state battery.